Mapping interpersonal violence against women in the District of Nias, 2009-2016 - Mita Yesyca; Formas Juitan Lase; Nenny Anggraini (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The research is about mapping interpersonal violence against women in the Nias District, North Sumatera. The patriarchal culture which has a hold in the area has significant effects on women. Using a social mapping approach and a feminist perspective, data in this research were collected through literature study, i.e. reports of service provider institutions on violence cases in Nias District, as well as observation and interview methods with local leaders in its ten sub-districts. The feminist perspective is useful to give voice to the unheard” female actors in a patriarchal society. Findings based on secondary data show that cases of violence in the Nias District from 2009-2016 fluctuated, with a total of 116 cases. The most frequent cases of violence experienced by women are physical violence, as many as 76 cases, sexual violence 31 cases, psychological violence eight cases and economic violence one case. The data collected from the interview and observation are 180 cases. The overall data show that physical violence occupies the highest number (secondary data 65.51% and primary data 53.88%) in the form of a beating received by the wife (domestic violence). The character of women’s vulnerability to violence varies ineach sub-district and is highly dependent on regional geographic-economic conditions. Therefore, the approach to the resolution of violence in each sub-district may vary. As a conclusion, the practice of violence against women in the Nias District is like an iceberg phenomenon that still needs to be followed up. The research also shows the potential of related institutions partnership, especially encouraged by churches, to end practices of interpersonal violence against women in the Nias District.